Compartmental analysis: a new approach to estimate protein breakdown and meal response in health and critical illness - Deutz, Nicolaas E. P.; Engelen, Mariëlle P. K. J. (Frontiers in Nutrition, 2024)
To discuss the use of the pulse stable isotope tracer approach to study changes in metabolism in healthy individuals and critically ill patients.We found that in the postabsorptive state and healthy condition, intracellular protein breakdown and net intracellular protein breakdown, when calculated using the pulse tracer approach in the healthy condition, is about double what has been reported in the past using the more traditional primed-constant and continuous stable isotope approaches ) (600 versus 300 grams of protein/day). In critically ill patients, protein breakdown is even higher and calculated to be around 900 grams of protein/day, using the pulse tracer approach. Based on these data we hypothesize that reducing protein breakdown in the postabsorptive state is key when trying to improve the condition of critically ill patients.Moreover, we also used the pulse tracer approach during feeding to better estimate the intracellular metabolic response to feeding. Our first observation is that endogenous protein breakdown does not seem to be reduced during feeding. We also have shown that when consuming a meal with a certain amount of protein, the biological value of that protein meal can be calculated with the pulse tracer approach.In conclusion, using the pulse stable isotope tracer approach to study protein kinetics in the postabsorptive state and during feeding expands our understanding of how dietary proteins can affect human protein metabolism. The intracellular protein synthesis stimulatory effect of a meal is an important factor to consider when calculating the exact protein requirements and needs particularly in critical illness.